MODEL SMART RELIGIOUS SCHOOL (SRS) DALAM PENGUATAN CITRA SMA NEGERI 2 SLEMAN SEBAGAI SEKOLAH RELIGIUS, HUMANIS, DAN INOVATIF - Marcelina Via Hanadya Safitri; Mohamad Joko Susilo (STKIP Pesisir Selatan, 2026)
This study aims to analyze the branding strategy of the Smart Religious School (SRS) Model in strengthening the image of SMA Negeri 2 Sleman as a religious, humanistic, and innovative school. This research employs a qualitative approach with a case study design to explore SMA Negeri 2 Sleman as a bounded system, allowing for an in-depth and context-rich understanding of the SRS Model as a school branding strategy. Data were collected through observation, documentation, and school digital media, which are considered sufficient to capture the conceptual implementation of the SRS Model. Data analysis was conducted using the interactive model by Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings indicate that the SRS Model serves as an effective branding strategy by integrating multidimensional intelligence (technological, spiritual, social, and emotional), embedding religious values across the educational system, and promoting sustainable digital innovation. The implementation of the SRS Model through school policies, work programs, budgeting, religious digital learning, and continuous evaluation significantly strengthens SMA Negeri 2 Sleman’s distinctive identity, differentiating it from other public schools.